The Impact of Management Information Systems on the Administrative Decision-Making Process – An applied study on administrative and technical personnel at King Abdul-Aziz University – - Al-Youbi, Bandar Mubarak; Khoualdi, Kamel Tahar (Journal of Economic, Administrative and Legal Sciences, 2021)
This study aimed at identifying the impact of management information systems on the administrative decision-making process at King Abdul-Aziz University in Jeddah from the administrative and technical staff standpoint who working at the university. In addition, to achieve this goal the descriptive and analytical approach was used. The problem of the study represents the challenges imposed by the external environment. The questionnaire initial data were distributed and (397) responses were obtained from the sample members. The study revealed several results that the most important to use programs related to management information systems which has a positive and effective impact on decision-making at King Abdul-Aziz University. Based on the results of the study, presenting a number of recommendations, involving the necessity to build databases for management information systems that can be referred to at any time to support administrative decision-makers and employee use them in solving numerous work problems.
Keywords: information systems; management information systems; administrative decision-making; decision-making support systems